Determination of N-nitrosamines by using triple quadrupole gas chromatography mass spectrometer EXPEC G-Chrom MS - article Editorial (Разработка и регистрация лекарственных средств)
Pharmaceuticals and medicines play an important role in maintaining human health. However, like any other products, they may contain potentially dangerous substances the so-called genotoxic impurities which can harm human health when consumed, so quality control of pharmaceutical products is of particular importance. Genotoxicity is the ability of a substance to have an irreversible effect on the structure and functions of DNA in cells thereby causing DNA death and errors in its replication, mutations and chromosomal aberrations. One of these substances is N-nitrosamines, which are formed as a result of the interaction of secondary amines with nitrites or nitrates. The Labconcept Group is the official distributor of leading manufacturers of analytical and general laboratory equipment. The Labconcept offers comprehensive solutions for equipping laboratories of various fields, including for the pharmaceutical industry. In this article, we will consider the possibility of determining such impurities using the EXPEC G-Chrom MS triple quadruple gas mass spectrometer using N-nitrosamines as an example.